Loop-mediated isothermal amplification of the toxR gene coupled with Lateral Flow Dipstick (LAMP-LFD) for the novel, rapid and specific visual detection of Vibrio harveyi - Ahmad Mukhlis Abdul Rahman; Julian Ransangan; Vijay Kumar Subbiah (Malaysian Society for Microbiology, 2023)
Aims: Vibrio harveyi is a serious pathogen for marine organisms particularly in hatcheries and grow-out ponds that attack their immune system. The rapid detection of V. harveyi is urgently needed to prevent bacterial spread. Here we described a rapid and specific visual detection method based on the Loop-Mediated Isothermal Amplification in combination with Lateral Flow Dipstick (LAMP-LFD). Methodology and results: A set of six novel primers were designed to target the toxR gene. These include the biotinlabelled inner primer that complements specifically to the target sequences. The resulting biotinylated LAMP amplicons were hybridised to the FAM-labelled probe resulting in lateral flow detection on the dipstick. The addition of loop primers improved the reaction time of LAMP by more than half and rapid detection was observed within 10-15 min. In comparison, the sensitivity of PCR-UV analysis was only at 104 copies while LAMP-LFD was able to detect lower amounts at 103 copies. The LFD provided higher specificity and selectivity since hybridization with specific probes to the LAMP amplicons was employed. In addition, detection of V. harveyi infected grouper was successful using the LAMPLFD method described here. Conclusion, significance and impact of study: LAMP-LFD is specific to V. harveyi. Our method provides a useful tool to rapidly detect and monitor the outbreaks of the pathogen.